Exams routine in attention to the prenatal care after the implementation of the paranaense mother network program - Helder Ferreira; Inês Angelica Novelli; Andrea Ferreira Ouchi França; Sebatião Caldeira; Rosane Meire Munhak Silva (Universidade Federal de Santa Maria, 2017)
Aim: to know the perceptions of health professionals and managers about the routine of examinations in prenatal care after the implantation of the Rede Mãe Paranaense Program. Method: qualitative research, conducted in the first semester of 2015, through interviews with 19 professionals working in Primary Health Care services in municipalities of the ninth Regional Health Service of Paraná, Brazil. Thematic analysis was used to analyze the results. Results: the nurse is primarily responsible for requesting the exams, the pregnant women have access to the laboratory exams, but the challenge remains in the release of the imaging exams. The difficulties were centered in the attention to brasiguaias, in the counter reference on the part of the high risk hospital, cost of the examinations, medical resistance in requesting some examinations, lack of resources and organization of the work. Final considerations: the program enabled improvements in the routine of exams. However, the difficulties that were highlighted may compromise attention to prenatal care.